„Безмерно счастлив”. O adwerbialnych wykładnikach wysokiego stopnia intensywności emocji w języku rosyjskim i polskim - Czapiga, Zofia (Studia Rossica Posnaniensia, 2018)
The paper is devoted to adverbial markers of the high level of emotions in Russian and Polish. The following types of intensifiers are analysed: очень, безмерно, крайне, невероятно, невыносимо, необыкновенно, несказанно, сильно, смертельно, страш- но, ужасно, чертовски, чрезвычайно; bardzo, nieprawdopodobnie, niewiarygodnie, niezmiernie, niezwykle, ogromnie, okropnie, piekielnie, potwornie, straszliwie, strasznie, szalenie. They express the level of emotional intensity in a way that is above average. They refer to the emotional state named by an adjective or a participle, an adverb (predicative), or a verb. Most of them serve to intensify both positive and negative emotions.